Tingkat Kepuasan Masyarakat Terhadap Pelayanan Pembayaran Pajak Kendaraan Bermotor Berbasis Aplikasi Signal Di Kantor Samsat Kota Tanjungpinang - Marnia Marnia; Fitri Kurnianingsih; Erva Afriyana; Dedek Hardiyanti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The implementation of both private and public organizations requires innovation to operate. Because the innovation of motor vehicle tax payment services based on signal applications at the Tanjungpinang city samsat office is a necessity for government organizations, along with increasing public pressure to improve the performance of government agencies in order to solve problems in people's lives through programs and services at the Tanjungpinang city samsat office. The quality of public services is determined by the service provider so that it can be understood that public services serve the community and must be provided adequately in order to meet the factors and indicators that determine the quality of public services. Innovation in government agencies is needed to provide public services through the development of new methods and new resources. Innovation of motor vehicle tax payment services based on signal applications at the samsat office as an E-Government-based public service strategy for vehicle tax payments. E-Government provides public services that can be accessed 24 hours a day, from anywhere, and at any time. E-Government also allows public services to be completed in a non-face-to-face manner, making it a more efficient service. The Indonesian government has realized the tremendous benefits of e- Government since 2003 has issued a policy of implementing e- Government in the form of Presidential Instruction No. 3 Year 2003. Recently, a technology based on the SIGNAL application has emerged that can run on Android and IOS. SIGNAL is a national digital Samsat application that allows Indonesian citizens to certify Annual STNK, Pay Motor Vehicle Tax (PKB), and pay Road Traffic Accident Fund (SWDKLLJ) online by issuing digital documents in the form of electronic certificates and can easily make mandatory contributions to, POLRI, E-TBPKP (Provincial Bapenda), and E-KD, (PT. Jasa Raharja). The implementation of the online system allows people to save more money and time by paying taxes online.